2015
DOI: 10.1039/c5ra15261e
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation improves the functional characteristics of chlorogenic acid–lactoferrin conjugate

Abstract: In the present study, a chlorogenic acid (CA)-lactoferrin (LF) conjugate prepared via alkali treatment was glycoslated with glucose (Glc) or polydextrose (PD) by the Maillard reaction. Formation of the covalent CA-LF-Glc/PD ternary conjugates was confirmed by matrix-assisted laser desorption/ionization timeof-flight mass spectrometry (MALDI-TOF-MS), Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC) and fluorescence analyses. The results showed that the grafting ratio betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 66 publications
(142 reference statements)
1
16
0
Order By: Relevance
“…Covalentm odification of lactoferrin with CGA at same pH (pH 9) showed as imilari ncrease in overall absorbance of protein, accompanied by the appearance of as houldera t 324 nm, [36] thus it can be concludedt hat the increasing number of bound phenolic moleculesl ies behind this peak since the unboundp henols were removed by dialysis. To exclude the possibility of absorbance increased ue to attached polymerization products of CGA oxidation, the UV/Vis spectra of CGA was recorded both at pH 7( where it is not oxidized) and pH 9( where oxidation is expected).…”
Section: Changesi Nuv/vis Absorbancementioning
confidence: 91%
“…Covalentm odification of lactoferrin with CGA at same pH (pH 9) showed as imilari ncrease in overall absorbance of protein, accompanied by the appearance of as houldera t 324 nm, [36] thus it can be concludedt hat the increasing number of bound phenolic moleculesl ies behind this peak since the unboundp henols were removed by dialysis. To exclude the possibility of absorbance increased ue to attached polymerization products of CGA oxidation, the UV/Vis spectra of CGA was recorded both at pH 7( where it is not oxidized) and pH 9( where oxidation is expected).…”
Section: Changesi Nuv/vis Absorbancementioning
confidence: 91%
“…In our recent studies, we have prepared protein–polyphenol–polysaccharide conjugates as multifunctional surface‐active ingredients (Liu and others , ). Ternary conjugates composed of lactoferrin, polydextrose, and chlorogenic acid were prepared via alkaline treatment and the Maillard reaction (Figure ).…”
Section: Conjugation Mechanismsmentioning
confidence: 99%
“…Proteins absorb UV light at 280 and 200 nm, due to the absorption of aromatic amino acids and the absorption of peptide bonds, respectively. Several authors have reported UV-Vis signatures of Tf [36] and Lf (Figure 1 A of [37]) and both ligands have similar relatively higher absorption at 280 nm. As Tf and Lf are proteins of the same family with similar shape, similar absorbance signatures were anticipated around 280 nm in Tf-tagged and Lf-tagged as well as Tf+Lf-tagged formulations.…”
Section: Liposome Development and Characterizationmentioning
confidence: 94%